Aplikasi Game Simulasi 3D Pencegahan Bullying Anak Remaja Berbasis Role Playing Menggunakan Metode FSM dan BT - Dwi Prasetyo, Septian; Vitianingsih, Anik Vega; Choiron, Achmad; Cahyono, Dwi; Wikaningrum, Anggit (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The case of bullying among teenagers has become one of the most concerning problems in society. Therefore, innovative and interesting approaches need to be taken to overcome this. The development of multimedia game technology can be an innovation that can be offered to prevent the impact of bullying cases on adolescents. The purpose of this research is to develop a 3D simulation game application for bullying prevention based on role playing using finite state machine (FSM) and behavioral tree (BT). FSM is used for the control system on the player, while BT is used to control the behavior of Non-Player Character (NPC) through the level of decisions and actions that must be taken or executed. This research methodology uses multimedia development life cycle (MDLC), namely, determining game concepts, creating design scenarios, collecting asset materials, developing game applications, testing game applications, and distributing game applications. The test results using the Technology Acceptance Model (TAM) get a percentage value of 76%. The development of role playing-based bullying prevention simulation game applications in research is expected to be an alternative learning simulation media that is effective in preventing bullying for teenagers